PENGEMBANGAN ALAT PERAGA AIR MANCUR SEDERHANA UNTUK MENINGKATKAN MINAT DAN MOTIVASI BELAJAR PADA MATERI HUKUM BOYLE - Dimas Aji Pangestu; Riki Perdana (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2023)
This study aims to develop teaching aids in the form of a simple fountain to increase interest and motivation in learning Boyle's law material. The research method used is the 4D method. then conduct a feasibility test using a questionnaire with an instrument consisting of 11 questions, 3 aspects, and 11 indicators. The three main aspects tested were feasibility, material suitability, and effectiveness, each of which earned a total score of 3.48, 3.51, 3.57 from the maximum score of 4.0. Based on the results of the due diligence which was attended by 64 respondents, the development of a teaching aid in the form of a simple fountain to increase interest and motivation in learning about Boyle's law material is very good so it is feasible to be used as a learning medium. However, it is necessary to emphasize the concept of Boyle's law so that the benefits of learning that students get can be felt.